Grey and white matter abnormalities in chronic obstructive pulmonary disease: a case–control study - Zhang, Haiyan (BMJ Group, 2012)
OBJECTIVES: The irreversible airflow limitation characterised by chronic obstructive pulmonary disease (COPD) causes a decrease in the oxygen supply to the brain. The aim of the present study was to investigate brain structural damage in COPD. DESIGN: Retrospective case–control study. Patients with COPD and healthy volunteers were recruited. The two groups were matched in age, gender and educational background. SETTING: A hospital and a number of communities: they are all located in southern Fujian province, China. PARTICIPANTS: 25 stable patients and 25 controls were enrolled from December 2009 to May 2011. METHODS: Using voxel-based morphometry and tract-based spatial statistics based on MRI to analyse grey matter (GM) density and white matter fractional anisotropy (FA), respectively, and a battery of neuropsychological tests were performed. RESULTS: Patients with COPD (vs controls) showed decreased GM density in the limbic and paralimbic structures, including right gyrus rectus, left precentral gyrus, bilateral anterior and middle cingulate gyri, bilateral superior temporal gyri, bilateral anterior insula extending to Rolandic operculum, bilateral thalamus/pulvinars and left caudate nucleus. Patients with COPD (vs controls) had decreased FA values in the bilateral superior corona radiata, bilateral superior and inferior longitudinal fasciculus, bilateral optic radiation, bilateral lingual gyri, left parahippocampal gyrus and fornix. Lower FA values in these regions were associated with increased radial diffusivity and no changes of longitudinal diffusivity. Patients with COPD had poor performances in the Mini-Mental State Examination, figure memory and visual reproduction. GM density in some decreased regions in COPD had positive correlations with arterial blood Po(2), negative correlations with disease duration and also positive correlations with visual tasks. CONCLUSION: The authors demonstrated that COPD exhibited loss of regional GM accompanied by impairment of white matter microstructural integrity, which was associated with disease severity and may underlie the pathophysiological and psychological changes of COPD.